2014
DOI: 10.1590/1678-775720140055
|View full text |Cite
|
Sign up to set email alerts
|

Does the number of implants have any relation with peri-implant disease?

Abstract: ObjectiveThe aim of this study was to evaluate the relationship between the number of pillar implants of implant-supported fixed prostheses and the prevalence of periimplant disease.Material and MethodsClinical and radiographic data were obtained for the evaluation. The sample consisted of 32 patients with implant-supported fixed prostheses in function for at least one year. A total of 161 implants were evaluated. Two groups were formed according to the number of implants: G1) ≤5 implants and G2) >5 implants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
1
27
1
2
Order By: Relevance
“…Additionally, in the present study individuals with four implants or more presented approximately two times higher probability of having peri‐implantitis. Corroborating the findings of previous studies that described that a higher number of rehabilitated implants increased the risk of peri‐implantitis because provides more sites accessible to biofilm and susceptible to peri‐implant lesions …”
Section: Discussionsupporting
confidence: 79%
“…Additionally, in the present study individuals with four implants or more presented approximately two times higher probability of having peri‐implantitis. Corroborating the findings of previous studies that described that a higher number of rehabilitated implants increased the risk of peri‐implantitis because provides more sites accessible to biofilm and susceptible to peri‐implant lesions …”
Section: Discussionsupporting
confidence: 79%
“…Passoni et al. . evaluated the number of implants compared with peri‐implant disease and found that patients that were rehabilitated with more than five implants had a higher prevalence of peri‐implant disease.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of these diseases has been reported to cause failures and can lead to implant loss; these lesions are commonly asymptomatic and frequently detected in follow‐up visits (Passoni et al. ). Dental plaque accumulation, poor oral hygiene (Ferreira et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…inflammation and marginal bone loss 1,30. So even though,10.7% of the treated cases showed BOP in the follow-up evaluation, this positive parameter was not considered as presence of disease since it was not correlated with other inflammation and bone loss signs in the treated implants.Furthermore, various studies have claimed that one of the main etiological factors of PI is plaque accumulation 4,5,31,32. This study considered a surgical anti-biofilm strategy to eliminate or ameliorate this etiologic condition.…”
mentioning
confidence: 99%